A Need Analysis of Blended Learning Model for Deaf Students in Higher Education - Utami, Iga Setia; Budi, Setia; Nurhastuti, Nurhastuti (Universitas Hamzanwadi, 2020)
Student diversity is one of the demographic advantages of education. One type of diversity is the registration in higher education students with special needs. For this purpose, teachers as educators are expected to be able to provide all students with adaptive teaching. Although the number of students with special needs is still a minority, educators still need to provide full education for them. Appropriate teaching can be achieved with the use of information technology, in particular the Internet. The use of the Internet as a support for classroom activities can be realized in a blended learning model. However, for each model to be used, an analysis study needs to be performed in order to have optimum results. The purpose of this study is to recognize needs and to obtain information on a blended learning model for deaf students in higher education. Needs analysis is carried out by means of a survey approach using a questionnaire provided to deaf students. The data were analyzed descriptively. The results have shown that deaf students meet the criteria for the development of a mixed learning model. Based on the study, it was concluded that the blended learning model can be applied to deaf students.